2021
DOI: 10.1155/2021/6631805
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Therapeutic Potential of NADPH Oxidases in Ischemic Stroke‐Induced Oxidative Stress

Abstract: Stroke is a leading cause of death and disability in humans. The excessive production of reactive oxygen species (ROS) is an important contributor to oxidative stress and secondary brain damage after stroke. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme complex consisting of membrane subunits and cytoplasmic subunits, regulates neuronal maturation and cerebrovascular homeostasis. However, NADPH oxidase overproduction contributes to neurotoxicity and cerebrovascular disease. NADPH oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…NOX5 upregulation and activation is related with many different processes, including the unfolded protein response [ 39 ], the management of lipid accumulation and insulin sensitivity [ 40 ] or the inflammation via COX2 activation and PG pathway induction [ 22 ]. In this context, the COX2 pathway may lead to brain ROS accumulation during aging [ 41 ] or after stroke [ 42 ]. In this work, we found that cerebral NOX5 expression in our knock-in mice led to an increase in the COX2 mRNA levels compared to the Control Young group.…”
Section: Discussionmentioning
confidence: 99%
“…NOX5 upregulation and activation is related with many different processes, including the unfolded protein response [ 39 ], the management of lipid accumulation and insulin sensitivity [ 40 ] or the inflammation via COX2 activation and PG pathway induction [ 22 ]. In this context, the COX2 pathway may lead to brain ROS accumulation during aging [ 41 ] or after stroke [ 42 ]. In this work, we found that cerebral NOX5 expression in our knock-in mice led to an increase in the COX2 mRNA levels compared to the Control Young group.…”
Section: Discussionmentioning
confidence: 99%
“…VAS2870 is a pharmacological inhibitor of NOX and has been shown to decrease infarct volume, oxidative stress, neuronal apoptosis and BBB leakage [ 36 ]. Several new small-molecule NOX inhibitors have been recently identified, such as VAS2970, M13, GKT136901, ML090 and MLM171 [ 37 , 38 , 39 , 40 ]. They have the potential to reduce ROS production and inhibit brain tissue damage [ 40 ].…”
Section: Antioxidant Treatment Strategies Of Oxidative Stress In Strokementioning
confidence: 99%
“…Several new small-molecule NOX inhibitors have been recently identified, such as VAS2970, M13, GKT136901, ML090 and MLM171 [ 37 , 38 , 39 , 40 ]. They have the potential to reduce ROS production and inhibit brain tissue damage [ 40 ]. The NOX inhibitors are non-specific and not isoform selective, although it may not be particularly important in stroke treatment, the development of selective NOX inhibitors could provide information about the precise role of various NOX isoforms.…”
Section: Antioxidant Treatment Strategies Of Oxidative Stress In Strokementioning
confidence: 99%
“…Upon cerebral ischemia, the mitochondrial respiratory chain is damaged and ATP synthesis is reduced, which is accompanied by the excessive generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) [23]. In addition, activated microglia can increase the expression of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, inducing the generation of ROS [24,25]. ROS has been reported to accumulate in ischemic tissue; its strong oxidation ability leads to the peroxidation of lipids, proteins and unsaturated fatty acids on the basement membrane and destroys the blood-brain barrier (BBB), ultimately causing irreversible damages on nucleic acid and carbohydrate metabolism [26,27].…”
Section: Oxidative Stressmentioning
confidence: 99%